The encoded Cirebon mask materiality, flow, and meaning along Java's Islamic northwest coast - Ross, Laurie Margot (Studies on performing arts & literature of the Islamicate world, 2016)
"Situates masks and masked dancing in the Cirebon region of Java (Indonesia) as an original expression of Islam. This is a different view from that of many scholars, who argue that canonical prohibitions on fashioning idols and imagery prove that masks are mere relics of indigenous beliefs that Muslim travelers could not eradicate. Making use of archives, oral histories, and the performing objects themselves, Ross traces the mask's trajectory from a popular entertainment in Cirebon--once a portal of global exchange--to a stimulus for establishing a deeper connection to God in late colonial Java, and eventual links to nationalism in post-independence Indonesia"--